PJ Masks Save the Library - Pendergrass, Daphne (New York : Simon Spotlight, 2016)
Catboy, Owlette, and Gekko try to save the library from the villain Romeo, who is using a nefarious machine to erase the text from library books and replace it with his own photographs.
Based on the episode "Owlette and the Flash Flip Trip"
Keywords: Superheroes -- Juvenile fiction; Libraries -- Juvenile fiction; Readers (Primary)